Hepatic stellate cells secrete Ccl5 to induce hepatocyte steatosis - Byeong-Moo Kim (Nature Portfolio, 2018)
Abstract Non-alcoholic fatty liver disease (NAFLD) encompasses a wide spectrum of disease severity, starting from pure steatosis, leading to fatty inflammation labeled as non-alcoholic steatohepatitis (NASH), and finally fibrosis leading to cirrhosis. Activated hepatic stellate cells (HSCs) are known to contribute to fibrosis, but less is known about their function during NAFLD’s early stages prior to fibrosis. We developed an ex vivo assay that cocultures primary HSCs from mouse models of liver disease with healthy hepatocytes to study their interaction. Our data indicate that chemokine Ccl5 is one of the HSC-secreted mediators in early NASH in humans and in mice fed with choline-deficient, L-amino acid defined, high fat diet. Furthermore, Ccl5 directly induces steatosis and pro-inflammatory factors in healthy hepatocytes through the receptor Ccr5. Although Ccl5 is already known to be secreted by many liver cell types including HSCs and its pro-fibrotic role well characterized, its pro-steatotic action has not been recognized until now. Similarly, the function of HSCs in fibrogenesis is widely accepted, but their pro-steatotic role has been unclear. Our result suggests that in early NASH, HSCs secrete Ccl5 which contributes to a broad array of mechanisms by which hepatic steatosis and inflammation are achieved.